A ROUTE TO UNDERSTANDING SYMBOLS IN ALGEBRA: FROM REAL-LIFE SITUATIONS TO SYMBOLIC LANGUAGE - Milinković, Nenad; Maričić, Sanja; Kovacs , Elvira (Studies in Teaching and Education, 2025)
In this paper, the authors present a learning framework for introducing letters as symbols for the unknown and variable that is based on real-life situations, their modeling and translation into algebraic language. In the empirical part of the paper, we conducted research with the aim of investigating the effects of such an approach on the development of algebraic symbolism in the minds of the students in the lower grades of primary school. The research was conducted on a sample of 257 fourth-grade students of primary school in the Republic of Serbia, by using an experimental method with parallel groups. The research results show positive effects of the implemented approach on a better understanding of symbolic notation and a greater degree of algebraic generalization. These results confirm the hypothesis that introducing algebraic symbols through real-life problems and context-related activities can significantly improve students’ ability to correctly interpret and use algebraic notation.